Scalable Photocatalyst Panels for Photoreforming of Plastic, Biomass and Mixed Waste in Flow. Issue 19 (19th November 2020) - Uekert, Taylor; Bajada, Mark A.; Schubert, Teresa; Pichler, Christian M.; Reisner, Erwin
Abstract: Solar‐driven reforming uses sunlight and a photocatalyst to generate H2 fuel from waste at ambient temperature and pressure. However, it faces practical scaling challenges such as photocatalyst dispersion and recyclability, competing light absorption by the waste solution, slow reaction rates and low conversion yields. Here, the immobilisation of a noble‐metal‐free carbon nitride/nickel phosphide (CN x |Ni2 P) photocatalyst on textured glass is shown to overcome several of these limitations. The 1 cm 2 CN x |Ni2 P panels photoreform plastic, biomass, food and mixed waste into H2 and organic molecules with rates comparable to those of photocatalyst slurries. Furthermore, the panels enable facile photocatalyst recycling and novel photoreactor configurations that prevent parasitic light absorption, thereby promoting H2 production from turbid waste solutions. Scalability is further verified by preparing 25 cm 2 CN x |Ni2 P panels for use in a custom‐designed flow reactor to generate up to 21 μmolH 2  m −2  h −1 under "real‐world" (seawater, low sunlight) conditions. The application of inexpensive and readily scalable CN x |Ni2 P panels to photoreforming of a variety of real waste streams provides a crucial step towards the practical deployment of this technology. Abstract : Waste to fuel : Carbon nitride/nickel phosphide photocatalyst panels are prepared by a simple drop‐casting procedure and used to produce hydrogen fuel from a variety of plastic, biomass, food and mixed waste in an up‐scaled flow reactor.